Implementasi Model Pembelajaran Berbasis Proyek dalam Meningkatkan Kreativitas Siswa pada Mata Pelajaran Pendididikan Agama Kristen - Nunut Mardahai; Bangun Munthe; Imelda Butarbutar (CV. Creative Tugu Pena, 2024)
This research aims to determine the extent to which the project-based learning model is used to increase the creativity of students in class VIII Christian Religious Education at SMP YP Cerdas Mandiri. The type of research that will be used in this research is classroom action research (PTK). The place of research was YP Cerdas Mandiri Smp JL. Cemara Abadi, Sampali, District. Percut Sei Tuan, Deli Serdang Regency, North Sumatra 20371 In the odd semester of the 2023/2024 academic year. The population in this research is all students in class VIII of SMP YP Cerdas Mandiri, totaling 20 students, where students will study the existence of a project to recycle used goods into flowers by researchers to see the growth of student creativity, using the classroom action research method, in the learning process in class VIII SMP. This research consisted of 4 stages, namely planning, implementation, observation and reflection. Based on the results of the research and observations made by the researcher, it can be concluded that the implementation of the project-based learning model in increasing student creativity in the class VIII Christian religious education subject at SMP YP Cerdas Mandiri is said to be successful. The research results stated that the implementation of the project-based learning model showed an increase in student creativity from the value data obtained in the first cycle, the number of students who completed it was 8 students (40%). Meanwhile, in cycle II the number of students who completed was 16 students (80%), an increase from cycles I and II of 40%.